2014
DOI: 10.3177/jnsv.60.35
|View full text |Cite
|
Sign up to set email alerts
|

Food Restriction Causes Low Bone Strength and Microarchitectural Deterioration in Exercised Growing Male Rats

Abstract: SummaryThe pathogenesis of bone disorders in young male athletes has not been well understood. We hypothesized that bone fragility is caused by low energy availability, due to insufficient food intake and excessive exercise energy expenditure in young male athletes. To examine this hypothesis, we investigated the influence of food restriction on bone strength and bone morphology in exercised growing male rats, using three-point bending test, dualenergy X-ray absormetry, and micro-computed tomography. Four-week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
(45 reference statements)
1
7
0
Order By: Relevance
“…2). Our group reported that the combination of voluntary running exercise and food restriction resulted in low bone strength in young male rats [29], similar to finding in the present study with young female rats. Moreover, in the present study, the two-way ANOVA statistical methods, revealed that an interaction occurred as a result of combination of conditions.…”
Section: Discussionsupporting
confidence: 92%
“…2). Our group reported that the combination of voluntary running exercise and food restriction resulted in low bone strength in young male rats [29], similar to finding in the present study with young female rats. Moreover, in the present study, the two-way ANOVA statistical methods, revealed that an interaction occurred as a result of combination of conditions.…”
Section: Discussionsupporting
confidence: 92%
“…Epidemiological studies have reported that bone disorders are less frequent in male athletes than in female athletes. On the other hand, our data suggested that food restriction decreases bone strength due to cortical bone loss, although mechanical loading adds to bone strength in growing male rats 57) . Therefore, these data imply that low energy availability caused trabecular bone loss even though the experimental group underwent exercise training.…”
Section: Effect Of Inadequate Energy Intake and Physical Activitymentioning
confidence: 60%
“…Therefore, these data imply that low energy availability caused trabecular bone loss even though the experimental group underwent exercise training. In this study, low energy availability caused low BMD and microarchitectural deterioration in the growing male rats 57) . <Fig.…”
Section: Effect Of Inadequate Energy Intake and Physical Activitymentioning
confidence: 64%
“…This TRF regimen reduced body and liver weight gains (but not fat) and improved glucose tolerance. Similarly Hatori et al (2012) also limited feeding of a HFD (61%) to 8 hr during the dark period in B6 mice and noted reduced evidence of obesity, hyperinsulinemia, hepatic steatosis, and improved motor coordination with no differences in caloric intake (Hattori et al, 2014). The period of restricted feeding appears to be a critical element in the benefits of these regimens.…”
Section: How Important Is the Schedule Of Feeding?mentioning
confidence: 99%
“…Hattori et al investigated exercise initiated at 4 wk in male SD rats with and without 30% CR for 13 wks. They noted a reduction in femoral bone strength in rats in the exercised group on CR compared to control rats (Hattori et al, 2014). …”
Section: Are There Detrimental Effects Of Cr?mentioning
confidence: 99%